A hybrid assessment approach for medical device software development companies. Issue 7 (28th December 2017) - Özcan‐Top, Özden; McCaffery, Fergal
Abstract: Medical device software development organizations are bound by regulatory requirements and constraints to ensure that developed medical devices will not harm patients. Medical devices have to be treated as complete systems and be evaluated in this manner. Instead of manufacturers having to ensure compliance to various regulatory standards individually, the authors previously developed a medical device software process assessment framework called MDevSPICE ® that integrates the regulatory requirements from all the relevant medical device software standards. The MDevSPICE ® was developed in a manner that suits plan‐driven software development. To improve the usability of MDevSPICE ® in agile settings, we extended the assessment approach. The hybrid assessment approach described here combines the MDevSPICE ® ‐based process assessment method with steps for prioritization of improvement needs through value stream mapping and enabling process improvement through the use of KATA technique. This approach integrates agile methods into the medical device software development process while adhering to the requirements of the regulatory standards. This paper describes the implementation of the approach within 4 organizations that develop software in line with medical device regulations. Abstract : MDevSPICE ® is a medical device software process assessment framework. To improve the usability of MDevSPICE ® in agile settings, we extended the assessment approach. The hybrid process assessment approach described here combines the MDevSPICE ® ‐based process assessment method with steps for prioritization of improvement needs through value stream mapping and enabling process improvement through the use of KATA technique. The hybrid approach integrates agile methods into the medical device software development process while adhering to the requirements of the regulatory standards.